О подтверждении новой концепции о переходных процессах в электроцепях экспериментальными исследованиями - Божко, А.Е. (Видавничий дім "Академперіодика" НАН України, 2007)
The theoretical and experimental substantiation of expansions of input spasmodic voltages for electric circuits into two components is given. The first component is the sum of damping harmonics, and the second one is the exponentially increasing voltage.